SŁOWA˗WARTOŚCI: INTERKULTUROWOŚĆ UKRYTA W JĘZYKACH - Dryjańska, Agnieszka (Neofilolog, 2018)
The present paper attempts to investigate the developement of existential competence within the framework of the intercultural approach to foreign language teaching. The main dimension of this approach to be explored is the application of the semantic analysis of key words for each culture designating values. To better understand the theoretical background of the intercultural competence its main aspects will be analyzed, i.e. alterity, representation, and identity. The analysis will especially include the process of discovering the real meaning of words within their cultural background. Such a reflective approach to teaching and learning foreign languages allows the students to change their ethical attitude towards foreign cultures as well as their own culture.